EARLY POSTOPERATIVE NAUSEA AND VOMITING (EARLY PONV) IN PEDIATRIC PATIENTS AFTER GENERAL ANESTHESIA - Dita Apriliani; Septian Mixrova Sebayang; Budi Joko Santoso; Roro Lintang Suryani (Jurnal Keperawatan Sriwijaya, 2026)
Aim: This study aimed to determine the description of early postoperative nausea symptoms among pediatric patients at Prof. Dr. Margono Soekarjo Regional General Hospital, Purwokerto. Method: This study used a quantitative descriptive design with a total sampling technique involving 46 pediatric respondents aged 4–18 years who underwent surgery under general anesthesia. Nausea severity was assessed within the first 2 hours postoperatively (early PONV phase) using the Baxter Retching Faces (BARF) Scale, while vomiting events were recorded using an observation sheet. Data were analyzed using univariate analysis and presented as frequency and percentage distributions. Result: A total of 45 out of 46 patients (97.8%) showed postoperative nausea symptoms (BARF ≥1). The majority experienced mild to moderate nausea (60.9%), followed by severe nausea (37.0%), and vomiting (4.3%). Nausea symptoms were observed across all categories of age, sex, and duration of surgery, with higher intensity tendency in procedures with moderate to longer durations. Conclusion: Early postoperative nausea symptoms in pediatric patients showed a very high prevalence, predominantly characterized by mild to moderate nausea. These findings highlight the need to strengthen preventive and management strategies for early PONV in the pediatric population.